Student worksheets on environmental education based on project-based learning for the 4r topic in elementary school - Ilmi Zajuli Ichsan; Akhmad Subkhi Ramdani; Eny Purwanitiningsih; Santhi Pertiwi; Saat Safaat (STKIP Melawi, 2026)
The environmental problem, especially related to environmental education on the topic of reduce, reuse, recycle, replace (4R), is the learning problem for elementary school students. Project-based learning is very important to be developed in environmental education at the elementary school level, such as in grade IV. The development of student worksheets can be an innovation in developing environmental education that is more relevant to current conditions. The purpose of this study is to develop student worksheets based on project-based learning on the topic of the 4Rs for grade IV elementary school students. The research method used is research and development through the ADDIE approach. The results of this study show that the scores for the validated student worksheet products are 90.00% and 92.50%, indicating a very valid category and can be used in learning. The results of this study also confirm that efforts to develop student worksheets align with efforts to develop students’ 21st-century competencies. The conclusion of this study is that the innovation of student worksheets based on project-based learning on the topic of 4R can be used in learning in elementary school.